(untitled) - Paluchova, Anna (Aura musica, 2017)
The article Choir compositions of Vojtech Didi with accent to piece SINI AMORE NIHIL deals with choir pieces of this composer and deeply analyzes composition Sini amore nihil. The Article presents compositions and musical language of Vojtech Didi. The conclusion shows how are composer's choir pieces incorporated into the context of contemporary pieces of other composers in Slovakia and abroad. Assumed contribution of this paper is overview of work of Slovak composer Vojtech Didi with emphasis to his choir pieces.
Keywords: Vojtech Didi; choir; contemporary music; composition